Strategi Penerbitan Pers Dakwah di Mandailing Natal(Studi Kasus pada Media Mohganews) - Siti Sarah Lubis; Elismayanti Rambe (Jurnal Pendidikan dan Humaniora Rumbio, 2024)
Mohganews also focuses on increasing religious understanding, strengthening religious identity, supporting religious education, community economic empowerment, and increasing social and environmental awareness. The positive impact of this publishing strategy can be seen from increasing religious knowledge, forming an active reading community, and contributing to the social and economic welfare of the Mandailing Natal community. This research concludes that the innovative and adaptive publishing strategy implemented by Mohganews is effective in spreading da'wah messages and provides significant benefits to society. By continuing to adapt to technological developments and audience needs, it is hoped that Mohganews can continue to act as an agent of positive change in the spread of Islamic teachings and community development in Mandailing Natal. This research aims to examine the da'wah press publishing strategy implemented by Mohganews Media in Mandailing Natal. In the current digital era, da'wah media have an important role in spreading Islamic teachings and strengthening people's religious identity. Mohganews, as a local media that focuses on Islamic da'wah, has developed various strategies to achieve its goals. This research methodology uses a qualitative approach with a case study on Mohganews Media. Data was collected through in-depth interviews with the editor-in-chief and staff of Mohganews, as well as religious figures and loyal readers. Direct observations of operational activities and analysis of published content are also carried out to understand the strategies implemented. In addition, literature analysis is used to support research findings.